Peran Skrining Kadar Trigliserida dalam Upaya Menjaga Kualitas Kesehatan pada Kelompok Usia Dewasa di SMA Santo Yoseph, Cakung - Ruslim, Welly Hartono; Santoso, Alexander Halim; Gunaidi, Farell Christian; Setiawan, Fiona Valencia; Wijaya, Bryan Anna; Destra, Edwin (Universitas 45 Surabaya, 2024)
Hypertriglyceridemia is a condition characterized by triglyceride levels in the blood that exceed normal limits, which can increase the risk of cardiovascular disease and other metabolic disorders. This Community Service initiative aims to enhance understanding and awareness among adults regarding the risks of high triglyceride levels and preventive measures through routine screenings and health education. The method used is the Plan-Do-Check-Act (PDCA) approach, which includes planning, implementation, checking, and action stages. During the planning stage, objectives, educational materials, and facility preparations are established to support the activities. Implementation includes sessions on the risks of high triglycerides, healthy lifestyle practices, and participant triglyceride level screenings. The checking stage evaluates participant understanding and the effectiveness of the activities. The action stage involves refining educational materials based on participant feedback. Improving community understanding of the importance of maintaining triglyceride levels through a balanced diet, regular physical activity, and routine monitoring is essential to support preventive efforts against potential health issues arising from this condition in the future.